The Fugitive: A Play in Four Acts - Galsworthy, John, 1867-1933 (Salt Lake City, UT : Project Gutenberg, 2004)
"The Fugitive: A Play in Four Acts" by John Galsworthy is a dramatic work written during the early 20th century. The play delves into the complexities of marriage, societal expectations, and personal freedom, focusing on the strained relationship between the main character, Clare Dedmond, and her husband, George Dedmond. As Clare grapples with her unfulfilled desires and the confines of her domestic life, the play explores themes of self-identity and the quest for liberation. The opening of the play introduces us to the personal tensions within the Dedmond household. George arrives home to find that Clare has unexpectedly left for a walk, setting off a discussion with his parents about their troubled marriage. Their interactions reveal an undercurrent of discontent, with George expressing frustration over Clare$1 (Bs behavior and his family prompting him to be cautious about her friendship with a literary man named Malise. As the plot unfolds, Clare's internal struggles become increasingly clear; she seeks to break free from the conventional bounds of her life, feeling like a "prisoner" in her own home. This opening establishes the emotional stakes and conflicts that will drive the narrative forward, documenting the pressures of societal norms on personal happiness and the yearning for genuine connection. (This is an automatically generated summary.)s
Release date is 2004-09-26
Produced by David Widger
Keywords: English drama